Plotinus on Beauty Beauty as Illuminated Unity in Multiplicity - Gál, Ota (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2022)
Although Plotinus' two treatises on beauty could be taken to reflect an evolution in his thought, a careful examination shows that he consistently argues for a conception of beauty as the illuminated unity in multiplicity of the Intellect.